2014
DOI: 10.4238/2014.december.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization, expression, and immunological response analysis of the TWEAK and APRIL genes in grass carp, Ctenopharyngodon idella

Abstract: TWEAK and APRIL are important members of the TNF superfamily, which play a crucial role in several diseases. Here, we describe the identification of grass carp (Ctenopharyngodon idella) homologs of TWEAK and APRIL (designated gcTWEAK and gcAPRIL, respectively) and their response to Aeromonas hydrophila and Aquareovirus infection. The gcTWEAK cDNA sequence contains 2273 bases with an open reading frame of 753 bases encoding 250-amino acid residues. The gcTWEAK protein contains a predicted transmembrane domain, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 39 publications
(52 reference statements)
0
12
0
Order By: Relevance
“…Although APRIL is probably the most important B cell-regulating TNFSF together with BAFF, very little is known about fish APRIL. In fact, although BAFF homologs have been identified in many cartilaginous and bony fish (summarized in Table 3 ), only a few APRIL homologue sequences have been found in teleost, specifically in zebrafish, channel catfish, Atlantic salmon, rainbow trout ( 41 ), and grass carp ( 134 ) (Table 3 ). In addition, while BAFF is present in all vertebrates, APRIL is missing in cartilaginous fish, birds, and several bony fish ( 168 ).…”
Section: A Proliferation-inducing Ligandmentioning
confidence: 99%
See 2 more Smart Citations
“…Although APRIL is probably the most important B cell-regulating TNFSF together with BAFF, very little is known about fish APRIL. In fact, although BAFF homologs have been identified in many cartilaginous and bony fish (summarized in Table 3 ), only a few APRIL homologue sequences have been found in teleost, specifically in zebrafish, channel catfish, Atlantic salmon, rainbow trout ( 41 ), and grass carp ( 134 ) (Table 3 ). In addition, while BAFF is present in all vertebrates, APRIL is missing in cartilaginous fish, birds, and several bony fish ( 168 ).…”
Section: A Proliferation-inducing Ligandmentioning
confidence: 99%
“…This has encouraged evolutionary immunologists to hypothesize that since BAFF and APRIL have structural and functional similarities and share receptors, the absence of APRIL on cartilaginous fish or the loss of APRIL in avian species could have been functionally compensated by BAFF. From the functional point of view, teleost APRIL has been shown to be mostly expressed in lymphoid tissues (spleen, head kidney) as well as in some mucosal tissues (skin, intestine) but at very low levels ( 41 , 114 , 134 ). After a bacterial or a viral challenge, the transcription of APRIL was quickly upregulated in immune tissues of grass carp ( 134 ), and recombinant APRIL promoted the survival of total splenocytes in zebrafish ( 169 ), indicating that this TNF ligand plays some role on the activation of the immune response.…”
Section: A Proliferation-inducing Ligandmentioning
confidence: 99%
See 1 more Smart Citation
“…Although BAFF homologs have been identified in many cartilaginous and bony fish [summarized in Ref. ( 17 )], only a few APRIL homolog sequences have been found in teleost, specifically in zebrafish ( Danio rerio ) ( 18 , 19 ), channel catfish ( Ictalurus punctatus ) ( 18 ), Atlantic salmon ( Salmo salar ) ( 18 ), rainbow trout ( Oncorhynchus mykiss ) ( 18 ), and grass carp ( Ctenopharyngodon idella ) ( 20 ). Interestingly, while BAFF is present in all vertebrates, APRIL is missing in cartilaginous fish, birds and several bony fish, suggesting that in some animal groups BAFF might have functionally compensated the loss of APRIL ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning its transcriptional regulation, previous studies performed in grass carp have shown that APRIL transcripts are predominantly expressed in the skin, spleen, and anterior kidney in homeostasis ( 20 ). These levels of expression were significantly upregulated in most immune tissues in response to a bacterial or a viral infection ( 20 ), pointing to an important role of teleost APRIL in the initial stages of antiviral and antibacterial responses. Similarly, an infection with viral hemorrhagic septicemia virus induced the transcription of APRIL in rainbow trout peritoneal IgM + B cells along with that of TACI ( 22 ).…”
Section: Introductionmentioning
confidence: 99%